Lokalizacja i rozciągłość - Augustynek, Zdzisław (Filozofia Nauki, 1993)
The paper presents an outline of two related space-time notions: the notion of location and the notion of extension. The first notion concerns only physical objects, the second notion referrs also to space-time objects. The approach to both notions is here non-metric of - strictly speaking - topological. The construction is carried out within the ontology of point-eventism. Hence two problems appear immediately: the problem of location of certain sets and the problem of their extension. The reason is that according to the ontology of point-eventism all the physical as well as space-time objects - only point events excepted - are sets founded in such events. The author analyzes also the very relation between location and extension.